Aktivasi bentonit alam pacitan sebagai bahan penyerap pada proses pemurnian minyak sawit - Ailen Tanjaya; S Sudono; Nani Indraswati; Suryadi Ismadji (Jurnal Teknik Kimia Indonesia, 2006)
Application of pacitan's bentonite as adsorbent in purification process of palm oil. Bentonite is one of the widely use adsorbent which is usually used in the bleaching process of edible palm oil to remove pigments color and other impurities which can improve the sensory quality and the oxidative stability of the oil. Bleaching capacity from bentonite can be improved by acid activation, to modified the structure as well as to improve the sorptive surface area. The aim of this research was to determine the optimum acid concentration for the activation of bentonite from Pacitan, East Java. The bleaching capacity of activated bentonite was evaluated based on color, free fatty acid (FFA) and peroxide value (PV) contents of bleached palm oil. The activation was carried out using sulfitric acid (HSO) and hydrochloride acid (HCI) as activating agents at a ranges of concentrations from 1 N to 10 N. The bleaching process of crude palm oil was conducted at 100 C for 10 mins. The bleached palm oil were analyzed for its colur, free fatty acid (FFA) and peroxide value (PV) contents. From this study it can be concluded that the activation process using HCl 5 N gave the optimum bleaching capacity.Keywords: Bleaching earth; Acid activation; Bentonite; Color; Free fatty acid; Peroxide value AbstrakBentonit merupakan salah satu jenis adsorben yang sering digunakan pada proses bleaching minyak kelapa sawit untuk menyerap zat warna dan pengotor-pengotor dalam minyak. Kemampuan bleaching dari bentonit dapat ditingkatkan dengan aktivasi dengan asam untuk meningkatkan luas permukaan dan memodifikasi struktur bentonit. Tujuan dari penelitian ini adalah menentukan jenis dan konsentrasi asam yang optimum pada proses aktivasi bentonit Pacitan. Kemampuan bleaching bentonit dievaluasi berdasarkan parameter warna, kadar asam lemak bebas (Free Fatty Acid, FFA) dan bilangan peroksida (Peroxide Value, PV) pada bleached palm oil. Proses aktivasi bentonit dilakukan menggunakan asam sulfat (H2SO4) dan asam klorida (HCl) dengan variasi konsentrasi 1-10 N. Bentonit yang telah diaktivasi digunakan untuk proses bleaching degummed palm oil pad a suhu 100 C selama 10 menit. Bleached palm oil dianalisa warna (dengan lovibond tintometer), kadar FFA dan PV Dari hasil penelitian diperoleh bahwa bentonit Pacitan yang diaktivasi menggunakan HCl 5 N, memberikan hasil bleaching yang optimum.Kata kunci : Bleaching earth; Aktivasi asam; Bentonit; Wama; Asam lemak bebas; Bilangan peroksida